Oral antiviral drugs in experimental herpes simplex keratitis. - Kaufman, H E (1983)
Chronic oral administration of acyclovir or bromovinyl deoxyuridine to rabbits did not prevent recurrence of virus shedding or clinical corneal disease, nor did it alter the clinical course of recurrences of ocular herpetic disease or result in the appearance of resistant virus in tears.